1997
DOI: 10.1021/jf960846f
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Fermentation of Various Food Fiber Fractions

Abstract: Dietary fiber fractions (DFF) were fermented in vitro with human fecal inocula to study fiber fermentability and production of short-chain fatty acids (SCFA). Amylolytic and proteolytic enzyme treatment using the Association of Official Analytical Chemists enzymatic-gravimetric procedure reduced processed food fiber products to DFF by removing gastric enzyme-digestible (nonresistant) components. Total 24-h SCFA production from DFF decreased in the following order:  fig > oat = soy > pea > apple > corn = wheat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
49
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 17 publications
4
49
1
Order By: Relevance
“…Different types of indigestible carbohydrates give rise to different amounts and patterns of CAs during colonic fermentation, and it may therefore be possible to regulate the CA formation by diet. The CAs formed may depend on for example the monomeric composition of the carbohydrates, the type of linkages between the carbohydrate monomers, their solubility and their molecular weight (Berggren et al, 1993;Casterline et al, 1997;Bird et al, 2000;Karppinen et al, 2000;Henningsson et al, 2002Henningsson et al, , 2003Nilsson and Nyman, 2005). Studies examining CA formation have mainly been conducted in vitro by using human faecal inocula, or in vivo using animal models.…”
Section: Introductionmentioning
confidence: 99%
“…Different types of indigestible carbohydrates give rise to different amounts and patterns of CAs during colonic fermentation, and it may therefore be possible to regulate the CA formation by diet. The CAs formed may depend on for example the monomeric composition of the carbohydrates, the type of linkages between the carbohydrate monomers, their solubility and their molecular weight (Berggren et al, 1993;Casterline et al, 1997;Bird et al, 2000;Karppinen et al, 2000;Henningsson et al, 2002Henningsson et al, , 2003Nilsson and Nyman, 2005). Studies examining CA formation have mainly been conducted in vitro by using human faecal inocula, or in vivo using animal models.…”
Section: Introductionmentioning
confidence: 99%
“…Although the relative proportion of the organic end products from fermentation may vary, acetate is the major anion. Pectin is aparticularly good source for acetic acid (48,49), whilst arabinogalactan and guar gum are the poorest sources (48,50,51). By contrast, arabinogalactan and guar gum have been shown to give high amounts of propionic acid.…”
mentioning
confidence: 99%
“…Butyric acid production varies over a wide range. Starches have been shown to give high proportions of butyric acid in vitro (49,50,52). In humans it has been demonstrated that administration of an a-amylase inhibitor, acarbose, to subjects resulted in enhanced butyric acid in faeces, measured either as concentration or as percentage of total SCFAs (53).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of substrate reaching the colon may have been similar in both occasions; however, the profile of enriched SCFA in plasma differed depending on the test meal administered. On the basis of several studies suggesting that RS is a good source for butyrate production (Weaver et al, 1992;Casterline et al, 1997;De Schrijver et al, 1999;Brouns et al, 2002), we assumed a higher colonic 13 C-butyrate production after the barley kernel meal than after the porridge meal. Nevertheless, plasma 13 C-butyrate concentrations were rather similar after both meals.…”
Section: Discussionmentioning
confidence: 99%